Interplay Between the Autophagy-Lysosomal Pathway and the Ubiquitin-Proteasome System: A Target for Therapeutic Development in Alzheimer’s Disease - Bustamante, Hianara A.; González, Alexis E.; Cerda-Troncoso, Cristobal; Shaughnessy, Ronan; Otth, Carola; Soza, Andrea; Burgos, Patricia V. (Frontiers in Cellular Neuroscience, 2018)
Alzheimer’s disease (AD) is the most common cause of age-related dementia leading to severe irreversible cognitive decline and massive neurodegeneration. While therapeutic approaches for managing symptoms are available, AD currently has no cure. AD associates with a progressive decline of the two major catabolic pathways of eukaryotic cells—the autophagy-lysosomal pathway (ALP) and the ubiquitin-proteasome system (UPS)—that contributes to the accumulation of harmful molecules implicated in synaptic plasticity and long-term memory impairment. One protein recently highlighted as the earliest initiator of these disturbances is the amyloid precursor protein (APP) intracellular C-terminal membrane fragment β (CTFβ), a key toxic agent with deleterious effects on neuronal function that has become an important pathogenic factor for AD and a potential biomarker for AD patients. This review focuses on the involvement of regulatory molecules and specific post-translational modifications (PTMs) that operate in the UPS and ALP to control a single proteostasis network to achieve protein balance. We discuss how these aspects can contribute to the development of novel strategies to strengthen the balance of key pathogenic proteins associated with AD.